A comparison of physical activity, muscle strength, and sleep between people with type 2 diabetes in Kuwait and the UK: A cross-sectional study - Ebaa Al Ozairi; Ebaa Al Ozairi; Dalal Alsaeed; Dherar Al Roudhan; Nia Voase; Jill P. Pell; Frederick K. Ho; Mohammed Abdulla; Stuart R. Gray (Frontiers in Endocrinology, 2022)
BackgroundThe aim of the current study was to determine the prevalence of low muscle strength and to evaluate physical activity and sleep characteristics in people with type 2 diabetes in Kuwait. Additionally, equivalent data from the UK Biobank cohort were compared.MethodsPeople with type 2 diabetes from the UK Biobank (n = 23,570) and Kuwaiti cohorts (n = 3,135) were included in this cross-sectional study. Self-reported sleep, physical activity, and muscle strength were compared between the cohorts, using linear and logistic regression, with adjustments for age, sex, and duration of diabetes.ResultsPhysical activity levels (−1216 (−1328,1104 Met-min/wee k: standardized B-coefficient −0.52 (−0.57, −0.47) and grip strength (−3.2 (−3.58, −2.82) kg: standardized B-coefficient (−0.29 (−0.32, -0.26) were lower in the Kuwaiti cohort and the odds of having short sleep (OR 1.32 (1.19,1.46), being classed as inactive (OR 8.70 (7.59, 9.98) and having muscle weakness were higher (OR 1.88 (1.69, 2.09). These analyses were adjusted for age, sex, and duration of diabetes.ConclusionsThis study demonstrates that insufficient sleep, physical inactivity, and muscle weakness are prevalent in people with type 2 diabetes, especially in Kuwait. Importantly, these observations warrant urgent and effective interventions to improve sleep, muscle strength, and physical activity, especially in Kuwait.